Prospective memory in patients with Mild Cogntive Impairment - Cores, Evangelina Valeria (2023)
Prospective memory is the ability to remember to carry out intended actions and to evoke delayed intentions. It constitutes a crucial skill for the daily functioning of the elderly. It might also be prematurely compromised in neurodegenerative diseases. In the Latin American region, objective measures are not available for its assessment. The aim of this study is to explore prospective memory in patients diagnosed with Mild Cognitive Impairment. As specific aims, we intend to discriminate the performance on prospective memory between patients and healthy subjects and to study the internal consistency and inter-examiner reliability of the Mini Cóndor Test (a simplified version of a prospective memory test developed in Argentina). We carried out a comparative study including a group of 20 patients with Mild Cognitive Impairment and a group of 20 healthy subjects as control group. Results indicated significant statistically differences between groups in prospective memory performance in favor of the control group. The Mini Cóndor Test met adequate scores for internal consistency and inter-rater reliability. These preliminary results suggest that the Mini Cóndor Test has the potential to early detect cognitive impairment associated to neurodegenerative pathology.